Gastrointestinal co-digestion of wine polyphenols with glucose/whey proteins affects their bioaccessibility and impact on colonic microbiota. (May 2022) - Tamargo, Alba; Cueva, Carolina; Silva, Mariana; Molinero, Natalia; Miralles, Beatriz; Bartolomé, Begoña; Moreno-Arribas, M. Victoria
Graphical abstract: Highlights: Wine polyphenols reduce glucose bioaccessibility and α-lactalbumin digestibility. Co-digestion of wine with glucose/whey proteins influences polyphenols profile and concentration at colonic level. Co-digestion of wine and food matrices seems to affect colonic microbiota diversity and functionality. Unravelling food matrix effects will contribute to a better understanding of polyphenols bioactivity. Abstract: Interactions between food components during their gastrointestinal digestion are constant and could affect compounds digestibility and bioaccessibility. These interactions could have a key role in the bioactivity of dietary polyphenols. This study aimed to investigate the food matrix effects during the co-digestion of red wine with glucose and whey proteins using the gastrointestinal dynamic simulator simgi®. Bioaccessibility of wine polyphenols and nutrients and the effect of co-digestion on colonic microbiota composition and metabolism were evaluated. Co-digestion with red wine led to a reduction of over 50% of glucose bioaccessibility and lowered α-lactalbumin gastric degradation. Still, co-digestion with the food matrices modified polyphenols profiles, including their bioaccessible and non-bioaccessible fractions. For instance, the (−)-epicatechin bioaccessible fraction increased 70% when the wine was co-digested with glucose. Hence, the combined feeding of wine and each food matrix affected microbiota composition and functionality at colonic level. Glucose and whey proteins reduced bacterial diversity, but homogenization of beta-diversity by wine was observed. Moreover, wine presence favoured intestinal health-related taxa as Akkermansia or Bifidobacterium, and the co-digestion of wine and food matrices significantly increased total short- and medium-chain fatty acids production, especially butyric acid. Overall, this study provides evidence of the convenience of the simgi® system to evaluate the effects of co-digestion and highlights the importance of food matrix effects on our understanding of polyphenol bioactivity.